Addition of Amide Proton Transfer Imaging to FDG-PET/CT Improves Diagnostic Accuracy in Glioma Grading: A Preliminary Study Using the Continuous Net Reclassification Analysis - Sakata, A.; Okada, T.; Yamamoto, Y.; Fushimi, Y.; Dodo, T.; Arakawa, Y.; Mineharu, Y.; Schmitt, B.; Miyamoto, S.; Togashi, K. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Amide proton transfer imaging has been successfully applied to brain tumors, however, the relationships between amide proton transfer and other quantitative imaging values have yet to be investigated. The aim was to examine the additive value of amide proton transfer imaging alongside [18F] FDG-PET and DWI for preoperative grading of gliomas.MATERIALS AND METHODS: Forty-nine patients with newly diagnosed gliomas were included in this retrospective study. All patients had undergone MR imaging, including DWI and amide proton transfer imaging on 3T scanners, and [18F] FDG-PET. Logistic regression analyses were conducted to examine the relationship between each imaging parameter and the presence of high-grade (grade III and/or IV) glioma. These parameters included the tumor-to-normal ratio of FDG uptake, minimum ADC, mean amide proton transfer value, and their combinations. In each model, the overall discriminative power for the detection of high-grade glioma was assessed with receiver operating characteristic curve analysis. Additive information from minimum ADC and mean amide proton transfer was also evaluated by continuous net reclassification improvement. P < .05 was considered significant.RESULTS: Tumor-to-normal ratio, minimum ADC, and mean amide proton transfer demonstrated comparable diagnostic accuracy in differentiating high-grade from low-grade gliomas. When mean amide proton transfer was combined with the tumor-to-normal ratio, the continuous net reclassification improvement was 0.64 (95% CI, 0.036–1.24; P = .04) for diagnosing high-grade glioma and 0.95 (95% CI, 0.39–1.52; P = .001) for diagnosing glioblastoma. When minimum ADC was combined with the tumor-to-normal ratio, the continuous net reclassification improvement was 0.43 (95% CI, −0.17–1.04; P = .16) for diagnosing high-grade glioma, and 1.36 (95% CI, 0.79–1.92; P < .001) for diagnosing glioblastoma.CONCLUSIONS: Addition of amide proton transfer imaging to FDG-PET/CT may improve the ability to differentiate high-grade from low-grade gliomas.ADCminminimum ADCAPTamide proton transferAUCarea under the curveNRInet reclassification improvementROCreceiver operating characteristicS0 imagereference dataset acquired without presaturationSUVstandard uptake valueT/Ntumor-to-normal